Parents’ Communication Styles and Their Influence on the Adolescents’ Attachment, Intimacy and Achievement Motivation - Maximo, Sally I. (The Journal of Behavioral Science, 2011)
The study aims to know if the four parents’ communication styles – loving, assertive, aggressive and passive - have an influence on the adolescents’ attachment style, level of intimacy and achievement motivation. This descriptive-correlational study – with 251 SLU students as respondents - reveals that adolescents perceive their parents’ communication style as loving; whereas, aggressive and passive styles are less likely perceived. Both aggressive and passive communication styles are related to the different insecure attachments. Assertive style is related to dismissing attachment instead of a secure attachment as previously hypothesized. Males are more secure while females are more fearful in their attachments. While males are more achievement-oriented; females are more inclined for intimate connections. Results have implications on improving parent-adolescent relationships.